Dual-Band Singly-Fed Proximity-Coupled Tip-Truncated Triangular Patch Array for Land Vehicle Mobile System - Basari, Basari; Sumantyo, Josaphat Tetuko Sri (UI Scholars Hub, 2015)
This paper proposes a dual-band left-handed circularly polarized triangular-patch array that is developed for land vehicle mobile system aimed at mobile satellite communications. The array consists of six tip-truncated triangular patches, which the first three patches are used for reception and the second three patches are used for transmission purpose. Each of three-patches has a beam pattern that can be switched in three different 120°-coverage beam in azimuth-cut plane at a minimum targeted gain at a desired elevation angle. The targeted minimum gain of the array is 5 dBic, in order for data communications with a large geostationary satellite can be achieved. The array is able to operate in two different frequency bands i.e. 2.50 GHz band for reception (down-link) and 2.65 GHz band for transmission (uplink). The array is simulated using the Method of Moments-based software (Ansoft Maxwell), fabricated and measured to confirm the simulated results. The measurement results show that the 5dBic-gain and the 3dB-axial ratio of the reception elements cover all of 360° azimuth direction. In the case of transmission elements, 4.3dBic-gain and the 3dBaxial ratio can be obtained.